Comparison of the efficacy and feasibility of en bloc transurethral resection of bladder tumor versus conventional transurethral resection of bladder tumor: A meta-analysis. Issue 45 (November 2016) - Wu, Yu-Peng; Lin, Ting-Ting; Chen, Shao-Hao; Xu, Ning; Wei, Yong; Huang, Jin-Bei; Sun, Xiong-Lin; Zheng, Qing-Shui; Xue, Xue-Yi; Li, Xiao-Dong
Abstract: Background: The aim of this meta-analysis was to compare the feasibility of en bloc transurethral resection of bladder tumor (ETURBT) versus conventional transurethral resection of bladder tumor (CTURBT). Methods: Relevant trials were identified in a literature search of MEDLINE, EMBASE, Cochrane Library, Web of Science, and Google Scholar using appropriate search terms. All comparative studies reporting participant demographics, tumor characteristics, study characteristics, and outcome data were included. Results: Seven trials with 886 participants were included, 438 underwent ETURBT and 448 underwent CTURBT. There was no significant difference in operation time between 2 groups ( P = 0.38). The hospitalization time (HT) and catheterization time (CT) were shorter in ETURBT group (mean difference[MD] −1.22, 95% confidence interval [CI] −1.63 to −0.80, P < 0.01; MD −0.61, 95% CI −1.11 to −0.11, P < 0.01). There was significant difference in 24-month recurrence rate (24-month RR) (odds ratio [OR] 0.66, 95% CI 0.47–0.92, P = 0.02). The rate of complication with respect to bladder perforation ( P = 0.004), bladder irritation ( P < 0.01), and obturator nerve reflex ( P < 0.01) was lower in ETURBT. The postoperative adjuvant intravesical chemotherapy was evaluated by subgroup analysis, and 24-month RR in CTURBT is higher than that in ETURBT in mitomycin intravesical irrigation group ( P = 0.02). Conclusion: The first meta-analysis indicates that ETURBT might prove to be preferable alternative to CTURBT management of nonmuscle invasive bladder carcinoma. ETURBT is associated with shorter HT and CT, less complication rate, and lower recurrence-free rate. Moreover, it can provide high-qualified specimen for the pathologic diagnosis. Well designed randomized controlled trials are needed to make results comparable.